Correlation of Malnutrition Inflammation Score and Highly Sensitive C-reactive Protein with Mortality and Morbidity in Patients on Maintenance Hemodialysis in a Tertiary Care Center from South India – A Prospective Study - Pooja Prakash Prabhu; Vishwanath Siddini; Ravishankar Bonu; G. K. Prakash; Sankaran Sundar; Sudarshan Ballal (Indian Journal of Kidney Diseases)
Background: Patients undergoing maintenance hemodialysis have a high prevalence of protein energy malnutrition and inflammation. There are very few Indian studies which have looked into the utility of malnutrition inflammation score (MIS) in assessing the prognosis in dialysis patients. The objectives of this study were to assess the correlation of MIS with mortality and morbidity among hemodialysis patients and to compare it with highly sensitive C-reactive protein (hs-CRP). Methodology: MIS and hs-CRP were calculated for each patient at the beginning of the study and at the end of 12 months. Patients were followed up for 1 year and assessed for hospitalization rates, infection rates, erythropoietin requirements, cardiovascular events, cerebrovascular events, and mortality. Results: A very high mortality of 50% was noted with those who had MIS ≥10. MIS score of >7 was a strong predictor of 1-year mortality. There was an increased rate of hospitalization and infections noted in patients with higher MIS scores. There was a good correlation between MIS scores and hs-CRP among dialysis patients. Upon follow-up, there was a statistically significant difference in terms of serum albumin, hs-CRP, and hospitalization rates among those patients who continued to be in the low-risk group MIS (1–4) when compared to those who had worsening of their MIS scores at the end of 1 year. Conclusion: MIS is a good indicator of mortality and morbidity among dialysis patients. Periodic assessment of MIS score in the dialysis unit will enable us to risk stratify the patients and take necessary measures to improve their quality of life. By providing adequate dialysis, vascular access care, and nutritional support, it is possible to reduce the MIS and decrease the mortality and morbidity among hemodialysis patients.